Synthesis and Optical Characterization of Carbon Dot from Peels of Dragon Fruit and Pear - Hepriyadi, Selvy Uftovia; Isnaeni, . (Omega: Jurnal Fisika dan Pendidikan Fisika, 2018)
Fluorescence materials such as carbon dots are unique and non-toxic materials that can be produced using many methods. In this research, synthesis and optical characterization of carbon dots from the peels of dragon fruit and pear have been done. The synthesis uses bottom-up method using microwave with 20 minutes, 40 minutes, and 80 minutes of heating time. The result of optical characterizations showed that the samples that have been heat treated are carbon dots based of the absorbance in the range of 280-350 nm, and the intensity are decreased in the range of visible and infrared wavelength. There are emission and intensity changes by different heat treatments. From the samples of dragon fruits peels, the emission wavelength tended to shift toward visible light at the wavelength of 551.51 nm, 507.98 nm and 487.28 nm with the excitation at the wavelength of 420 nm from pulsed pico-laser. While, the emission wavelength from the samples of pears peels were fluctuate in wavelength of 529.09 nm, 507.52 nm and 519.46 nm. Similarly, the time-resolved photoluminescence characterization test showed that there were time changes in each sample of carbon dot. The decay lifetime of carbon dots was fluctuated between 4.5 ns - 5.4 ns for dragon fruitâs peels and about 1.9 ns - 2.4 ns for pears peels.